Investigation on the Influence of Microstructure Based on Hydrogen Bonding on Surface Tension by Raman Spectroscopy - Nannan Wu; Shunli Ouyang; Junjie Cui; Shiliang Liu; Mingzhe Zhang; Qingcheng Hu; Baokun Huang (International Journal of Analytical Chemistry)
Surface tension and Raman spectra containing hydrogen bonding in acetonitrile aqueous solutions with different mole ratios were obtained. Varied surface tension and hydrogen bonding in the mixed solution were discussed. For this purpose, the OH stretching bands were fitted into three Gaussian components to which different hydrogen-bonded water samples were assigned. Furthermore, the microstructures of binary solution were analyzed. The results indicated that the surface tension decreases dramatically with the enhancement of hydrogen bonds in the mixture. A spectroscopic method for studying the macroscopic properties of aqueous solutions was employed. The direct experiment results provided the relationship between surface tension and microstructure in aqueous solutions.